Systematic differences of gluteal muscle activation during overground and treadmill walking in healthy older adults. (February 2019) - Anders, Christoph; Patenge, Steffen; Sander, Klaus; Layher, Frank; Kinne, Raimund W.
Abstract: Guteal muscle activation during walkway and treadmill walking was compared by means of Surface EMG (SEMG). Healthy older adults (50–75 years, n = 54; 29 females, 25 males) walked on a walkway (WW) at their self-selected slow, normal, and fast walking speeds and on a treadmill (TM) at 2, 3, 4, 5, and 6 km/h. Subject-individual, best-matched speed pairs were constituted and named SLOW, NORMAL, and FAST. Hip muscle activation was measured on both sides at mid-distance between the greater trochanter and the iliac crest by applying eight equally-spaced bipolar SEMG channels from ventral to dorsal (P1–P8). Grand averaged amplitude curves and mean amplitudes over the complete stride were analyzed to compare WW and TM walking. TM walking evoked significantly elevated mean amplitude levels, particularly at the ventral positions P1 to P4, which were disproportionately increased at SLOW. In grand averaged curves, corresponding significant amplitude differences between WW and TM were observed during load acceptance (SLOW; NORMAL), mid-stance (all speeds), and late swing phase (SLOW), with the number of significant differences decreasing for all electrode positions from SLOW to FAST. Compared to WW walking, TM walking may thus require systematically elevated effort of gluteal muscles, in particular at slow walking speed.